In Vitro Model-Systems to Understand the Biology and Clinical Significance of Circulating Tumor Cell Clusters - May, Alexander N.; Crawford, Bryan D.; Nedelcu, Aurora M. (Frontiers in Oncology, 2018)
The isolation of clusters of circulating tumor cells (CTCs) from cancer patients has recently challenged the accepted view that the initiation of secondary tumors during metastasis involves the dissemination of individual cancer cells. As such clusters appear to be more aggressive than single tumor cells, CTC clusters are now considered a main player in the metastatic process, and many studies are exploring their diagnostic, prognostic, and clinical significance. However, several technical challenges limit advances in this area. Here, we suggest the use of established cancer cell lines that grow as cell clusters in suspension as a complementary approach that can help in understanding the biology of CTC clusters and their clinical significance. We argue that the many similarities between these “surrogate” clusters and the CTC clusters isolated from patients (e.g., in terms of size, morphology, heterogeneous expression of epithelial and mesenchymal markers, and type of cell–cell junctions) make these cell lines ideal systems for the development of strategies aimed at preventing or slowing down the metastatic process by targeting CTC clusters.